2017
DOI: 10.3390/met7110493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen on the Elastic and Anelastic Properties of the R Phase in Ti50Ni46.1Fe3.9 Alloy

Abstract: Abstract:The linear and non-linear internal friction, effective Young's modulus, and amplitude-dependent modulus defect of a Ti 50 Ni 46.1 Fe 3.9 alloy have been studied after different heat treatments, affecting hydrogen content, at temperatures of 13-300 K, and frequencies near 90 kHz. It has been shown that the contamination of the alloy by hydrogen gives rise to an internal friction maximum in the R martensitic phase and a complicated pinning stage in the temperature dependence of the effective Young's mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Anelastic properties of Ti-Ni-based alloys are widely explored, both for microstructural characterization of the alloys and for their application as high-damping materials [35]. Sapozhnikov et al investigated the linear and non-linear internal friction, effective Young's modulus, and amplitudedependent modulus defect of a Ti 50 Ni 46.1 Fe 3.9 alloy after different heat treatments, affecting hydrogen content [36]. They found that the internal friction maximum is associated with a competition of two different temperature-dependent processes affecting the hydrogen concentration in the core regions of twin boundaries.…”
Section: Contributionsmentioning
confidence: 99%
“…Anelastic properties of Ti-Ni-based alloys are widely explored, both for microstructural characterization of the alloys and for their application as high-damping materials [35]. Sapozhnikov et al investigated the linear and non-linear internal friction, effective Young's modulus, and amplitudedependent modulus defect of a Ti 50 Ni 46.1 Fe 3.9 alloy after different heat treatments, affecting hydrogen content [36]. They found that the internal friction maximum is associated with a competition of two different temperature-dependent processes affecting the hydrogen concentration in the core regions of twin boundaries.…”
Section: Contributionsmentioning
confidence: 99%